Ujaran Positif Dalam Unggahan Akun di Media Sosial Instagram @Biropsikologidinamis: Kajian Pragmatik - Nurmah Oktavia Anggraeni; Septi Aisah; Alvia Mirotul Khasanah; Sayyida Yusriyya; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Prima Pantau Putri Santosa (Lembaga Pengembangan Kinerja Dosen, 2024)
Speech acts are all actions carried out by someone in an interaction. The interaction that occurs between the first speaker and the second speaker during communication is two-way and reciprocal. However, interaction can also be done indirectly, for example interaction through posts on social media as in this research. This research aims to describe the form of positive speech in account uploads on the Instagram social media @biropsychologidinamis as a form of locutionary and perlocutionary speech acts. The method used in this research is a qualitative descriptive method. Data were collected using note-taking techniques and then analyzed to obtain the results of locutionary and perlocutionary speech acts. The research results show: a) The type of locutionary speech act consists of notification of information in the form of utterances in the form of positive words in each upload. b) Perlocutionary speech acts consist of the interlocutor's response to being influenced, doing something, accepting an invitation, making a request, giving an impression, making the interlocutor think, and attracting attention. c) Data analysis of social media account uploads regarding locutionary speech acts and perlocutionary speech acts. This research is useful for obtaining and adding further information in the field of pragmatics, especially about the types of locutionary and perlocutionary speech acts and the impact caused by these two utterances.